CONSTRUÇÃO DE MODELOS PARA AMBIENTES VIRTUAIS IMERSIVOS - BARBOSA, José Gabriel Ribeiro Capibaribe; MÜLLER, Raquel Marcia; FILHO, Rubens Barbosa; MÁRQUEZ, Mercedes Rocio; LIMA, André Chastel (ANAIS DO ENIC, 2026)
.